1994
DOI: 10.1007/bf00233706
|View full text |Cite
|
Sign up to set email alerts
|

Activation by hyperpolarization and atypical osmosensitivity of a Cl? current in rat osteoblastic cells

Abstract: During whole-cell recording of rat osteoblastic cells with high-Cl- internal solutions, 10 sec hyperpolarizing jumps from 0 mV induce a slow inward current relaxation, which is shown to be carried by hyperpolarization-activated Cl- channels. This relaxation increases and becomes faster with stronger hyperpolarizations. It is insensitive to Cs+ ions but is blocked in a voltage-dependent manner by 4,4'-diisothiocyanatostilbene-2,2'-disulfonic acid (DIDS) 1 mM and is reduced by 5-nitro-2-(3-phenylpropylamino) ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 56 publications
4
28
1
Order By: Relevance
“…An additional difference is that 9AC appeared to have a much slower onset of action than the other two compounds. A similar voltage-dependent effect of DIDS was observed for the hyperpolarization-activated chloride current in rat osteoblastic cells (Chesnoy-Marchais & Fritsch, 1994). We have found that DIDS is also an effective blocker of ClC_2 channels expressed in Xenopus oocytes.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…An additional difference is that 9AC appeared to have a much slower onset of action than the other two compounds. A similar voltage-dependent effect of DIDS was observed for the hyperpolarization-activated chloride current in rat osteoblastic cells (Chesnoy-Marchais & Fritsch, 1994). We have found that DIDS is also an effective blocker of ClC_2 channels expressed in Xenopus oocytes.…”
Section: Discussionsupporting
confidence: 80%
“…This current is not carried by cations since it was unaffected by agents which block hyperpolarization-activated cation currents such as IQ (Halliwell & Adams, 1982;Lamas et al 1997) or inwardly rectifying potassium currents (see Hille, 1992). Many of the properties of ICl,IR are, however, similar to other hyperpolarizationactivated chloride currents such as those that have been recorded in rat osteoblastic cells (Chesnoy-Marchais & Fritsch, 1994), T84 epithelial cells (Fritsch & Edelman, 1996) and Aplysia neurons (Chesnoy-Marchais, 1983). The threshold for activation of ICl,IR is within the range observed for the other currents and all of these currents exhibit inward rectification.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This increase in Na+/K+/2ClI cotransporter activity produces an increase in the Cl-content (Martinez et al, 1988), which gives rise to an increase in cell volume (Foskett, 1990). Native and expressed CIC-2 Cl-channels can apparently sense the internal Cl-concentration (Dinudom et al, 1993;Chesnoy-Marchais and Fritsch, 1994;Fritsch and Edelman, 1997) and the cell volume (GrOnder et al, 1992;Thiemann et al, 1992;Jordt and Jentsch, 1997). Channel activity increases as the Cl-concentration and the cell volume increase.…”
Section: Sympathetic 1-adrenergic Stimulationmentioning
confidence: 99%
“…To our knowledge, there are only few examples of native Cl − channels activated by external protons. The best studied pH-sensitive Cl − current is the inwardly rectifying Cl − channel ClC-2 for which numerous studies on both native and cloned channels indicated an extreme sensitivity to extracellular protons and an inhibition by Cd 2+ [30][31][32][33][34]. A recent study characterized an endogenous Cl − current in transformed human embryonic kidney HEK-293 cells, activated by extracellular pH [35].…”
Section: Discussionmentioning
confidence: 99%